2018
DOI: 10.3389/fendo.2018.00704
|View full text |Cite
|
Sign up to set email alerts
|

Role of Endocrine-Disrupting Engineered Nanomaterials in the Pathogenesis of Type 2 Diabetes Mellitus

Abstract: Nanotechnology has enabled the development of innovative technologies and products for several industrial sectors. Their unique physicochemical and size-dependent properties make the engineered nanomaterials (ENMs) superior for devising solutions for various research and development sectors, which are otherwise unachievable by their bulk forms. However, the remarkable advantages mediated by ENMs and their applications have also raised concerns regarding their possible toxicological impacts on human health. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 193 publications
0
7
0
Order By: Relevance
“…Apart from endocrine disruptive effects on sex hormones, particles may influence different metabolic pathways ( Priyam et al, 2018 ). Gurevitch et al (2012) demonstrated the potential role of titanium dioxide nanoparticles in the etiology of metabolic/endocrine disorders, such as obesity and insulin resistance.…”
Section: Toxicological Endpoints In the Particle Safety Assessmentmentioning
confidence: 99%
“…Apart from endocrine disruptive effects on sex hormones, particles may influence different metabolic pathways ( Priyam et al, 2018 ). Gurevitch et al (2012) demonstrated the potential role of titanium dioxide nanoparticles in the etiology of metabolic/endocrine disorders, such as obesity and insulin resistance.…”
Section: Toxicological Endpoints In the Particle Safety Assessmentmentioning
confidence: 99%
“…Work is ongoing by ECHA to develop classification and labelling criteria for endocrine disruption [ 278 ]. From a NM-perspective, there is increasing evidence showing endocrine disruption and reproductive impairments caused by NMs such as nano plastics [ 279 , 280 ], and this warrants further attention.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Disruption of the endocrine system leads to hormonal imbalance, which may influence the development and pathogenesis of metabolic disorders, particularly type 2 diabetes mellitus (Priyam et al, 2018).…”
Section: Type II Diabetes Mellitusmentioning
confidence: 99%
“…Titanium oxide nanoparticles (TiO2-NPs) and chromium nanoparticles (CrNano) affect insulin resistance in liver-derived cells causing increased production of insulin like molecules that cause reduced insulin sensitivity and devour the pathway. (Priyam et al, 2018) Cancer Meeker & Ferguson, (2012) have reported that phthalates found in plastics, medical applications, personal care products, home furnishings etc. are known to cause testicular and prostate cancer.…”
Section: Type II Diabetes Mellitusmentioning
confidence: 99%